Transforming Medical Education: A Need for Mandatory Faculty Development Program for Standardized Implementation of Family Adoption Program Across the Medical Colleges of the Country - Shikha, Swati; Kumar, Abhishek; Begum, Jarina; Ali, Syed Irfan (Indian Journal of Community Health, 2025)
Background: Since 2022, all medical schools across the country have included the Family Adoption Program (FAP) in their MBBS curricula as a component of competency-based medical education. Aims & objectives: To achieve uniformity in implementation of FAP across all the medical colleges of the country. Methodology: MBBS students are assigned to five families to form relationships, evaluate health, and improve medical care. The program has been implemented based on input from instructors and regulatory agencies, with NMC recommendations. Results: Since 2021, MBBS students have completed FAP, but variations exist across the country. A mandatory two-day training course is proposed for faculty members to ensure uniformity in implementation of family adoption program (FAP). Conclusion: The efficacy and consistency of the FAP would be improved by standardizing it through faculty training and consistent data reporting.